PENGARUH MOTIVASI BELAJAR, SELF CONTROL DAN CRITICAL THINKING TERHADAP PRESTASI BELAJAR MAHASISWA PRODI PENDIDIKAN EKONOMI STKIP PGRI SITUBONDO - Ahmad, Heffrizza (UNIVERSITAS NEGERI SURABAYA, 2017)
Learning achievement is one of the benchmarks of student ability. in this case affecting the learning achievement there are two external and internal. In this case the data obtained will be low while the liveliness of PGRI Situbondo STKIP students in the classroom as well as the development of data of graduates decreased levels of GPA. The purpose of this research that determines the effect of learning motivation, self-control and Critical Thinking on student achievement, economic education STKIP PGRI Situbondo. This research study Associative manifold with the causal relationship is causal with a quantitative approach. This study population is students of economics education study program STKIP PGRI force situbondo 2012, 2013, 2014, amounting to 210 students. Data collection method in this research is the method enclosed questionnaire that supported an open questionnaire on 138 samples. The test results indicate there are significant learning motivation on learning achievement, there is a self-control influence on learning achievement, and there is the influence of Critical Thinking on learning achievement. While simultaneously there are significant learning motivation, self-control and Critical Thinking on student achievement Prodi Economic Education STKIP PGRI Situbondo.